Auditoría energética del sistema eléctrico en la cooperativa San Francisco La Matriz y planteamiento de incorporación de un tablero de transferencia automática - Campos Freire, Celson Guillermo (2017)
San Francisco Ltda.”La Matriz”, Savings and Credit Cooperative with its headquarters is in Ambato , Tungurahua province, is a financial institution, not a bank with the objective to do carring out financial intermediation activities and social responsibility business associate. Currently, the San Francisco "La Matriz" saving and Credit Cooperative, being a financial entity with great economic fluidity in Ambato, presents an electrical system of very low reliability, by which an energy audit is carried out evaluating the electricity supply, Had had approximately 30 years of functionality and the lack of knowledge of the state, of the electrical diagram per floor, single line for which it was required a laborious work of information gathering of connections and identification of phases per floor to establish the current diagram and a current diagnosis of it’s installations. For the verification of the light status in each job, the data is collected and register correctly with the calibrated equipment, at the same time, a lighting simulation is performed for each workstation. Being considered under standards and luminaires that exist in the Market through DIAlux software, consequently is realized an economic technical analysis of the change of fluorescent luminaires to Led, in all the edifice. It is considered if the caliber of conductor is the appropriate, validating it’s technical characteristics, of operability, which are determined under calculations.. The results are interpreted using the Power Log 5.3 software. Respect to the electrical quality supply, considering voltage, current, power, power factor, flickers, harmonic levels, based on regulations recommended by the software, those established inside Ecuador and international, these data’s were collected for 7 days from on May 29 to June 5 by the Fluke 435-II Network Analyzer. It is considered to make the respective load balance diagram, for which a plane is made. A thermographic analysis under norm (NETA) is performed for the verification of the temperature level by the conductors and elements of the main board electric considering the time of analysis when it´s a load maximum with the help of SmarView 3.14 software. For the future implementation of the automatic transfer board, between the electricity supply of the Electricity Company Ambato and the generator of the savings and Credit Cooperative San Francisco Ltda.”La Matriz it has been made the calculations, logo programming, electrical diagram and quotes of the possible materials to be implemented were carried out.